2019
DOI: 10.3390/min9030162
|View full text |Cite
|
Sign up to set email alerts
|

Geological, Mineralogical and Textural Impacts on the Distribution of Environmentally Toxic Trace Elements in Seafloor Massive Sulfide Occurrences

Abstract: With mining of seafloor massive sulfides (SMS) coming closer to reality, it is vital that we have a good understanding of the geochemistry of these occurrences and the potential toxicity impact associated with mining them. In this study, SMS samples from seven hydrothermal fields from various tectonic settings were investigated by in-situ microanalysis (electron microprobe (EMPA) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS)) to highlight the distribution of potentially-toxic trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 154 publications
(307 reference statements)
0
15
0
Order By: Relevance
“…In modern hydrothermal settings, studies presenting trace element data of chalcopyrite are predominantly restricted to submarine hydrothermal environments, i.e., seafloor massive sulfides and active hydrothermal chimneys. For example, previous studies have reported LA-ICP-MS data showing that chalcopyrite from black smoker vents can host variable amounts of Zn, As, Sb, Ag, Pb, Bi, Se, Te, Co, and Ni, among other trace elements [12,[20][21][22][23][24][25][26]. Furthermore, [27] presented micro-analytical data of chalcopyrite retrieved from drill cuttings at the seawater-dominated Reykjanes geothermal system in Iceland.…”
Section: Introductionmentioning
confidence: 94%
“…In modern hydrothermal settings, studies presenting trace element data of chalcopyrite are predominantly restricted to submarine hydrothermal environments, i.e., seafloor massive sulfides and active hydrothermal chimneys. For example, previous studies have reported LA-ICP-MS data showing that chalcopyrite from black smoker vents can host variable amounts of Zn, As, Sb, Ag, Pb, Bi, Se, Te, Co, and Ni, among other trace elements [12,[20][21][22][23][24][25][26]. Furthermore, [27] presented micro-analytical data of chalcopyrite retrieved from drill cuttings at the seawater-dominated Reykjanes geothermal system in Iceland.…”
Section: Introductionmentioning
confidence: 94%
“…Enhanced oxidation of copper sulfides and copper dissolution in galvanic cells (as well as zinc, lead, and cadmium) during mining operations (Fallon et al, 2017;Knight et al, 2018), together with known toxic effects of soluble copper (Flemming and Trevors, 1989;Stohs and Bagchi, 1995;Simpson and Spadaro, 2016), suggest the potential for geochemical modification/degradation of the environment. The toxicity of sulfides differ from one place to another, depending on their geological setting, mineralogy, and crystalline texture (Fallon et al, 2019). Based on limited laboratory experiments, metal toxicity has been considered to be minor relative to the physical impacts of mining (Simpson and Spadaro, 2016;Knight et al, 2018), but this perspective does not take into account ecotoxicological effects in the pelagic environment, and empirical evidence in the field supporting this view is lacking.…”
Section: Mining Impacts On Inactive Sulfide Ecosystemsmentioning
confidence: 99%
“…where R is the UCS of SMS, MPa; P is the failure load, N; A is the cross-section area perpendicular to the loading direction, mm 2 . During the UCS test, the static deformation parameters can be measured synchronously to obtain the strain-variable and calculate the elastic modulus E and Poisson's ratio µ.…”
Section: Ucs Testmentioning
confidence: 99%
“…Seafloor Massive Sulfides (SMS), formed by the hydrothermal or chemical processes on the seafloor, are rich in precious and base metals such as gold, silver, manganese, iron, cobalt, etc. [1][2][3][4][5]. Currently, SMS deposits are primarily exploited by a spiral drum with cutting picks.…”
Section: Introductionmentioning
confidence: 99%